Eco-innovation in Tourism. A Research Agenda Around Public Policies - Hernandez-Sanchez, Alexis-Ricardo (2023)
In this article a literature review is carried out with the aim of analysing the current state of research on public policies on eco-innovation in tourism, to provide a knowledge base on the potential and nature of this object of study. A content analysis of the publications in the Web of Science database was carried out. Starting from open-access articles under a structured search equation, 182 articles from the period between 1991 and 2021 were identified; these were subsequently analysed and classified under the Cloud of Science and Tree of Science software. The results show that the study of eco-innovation and its relationship with public policies in tourism contexts is most advanced in Asian countries, and the literature in Latin American contexts is still at an incipient stage. Research on policies that promote environmental care and regulatory policies that improve ecological processes is identified, highlighting the importance of practices and operational factors. It is concluded that studies on remedial, punitive, and macro-regulatory policies for environmental science and technology are absent.